Recurrent Bell’s palsy: outcomes and correlation with clinical comorbidities - MANCINI, P. (Acta Otorhinolaryngol Ital, 2019)
Recurrent Bell’s palsy (RBP) has been reported to range from 2.6 to 15.2% of primary Bell’s palsy (BP) and has been associated with systemic comorbidities such as diabetes and hypertension. A retrospective analysis of patients affected by BP and RBP were performed to define the signs and symptoms associated with recurrence and the outcomes. Clinical and subjective characteristics of 341 patients affected by facial palsy were analysed. Facial function was assessed via House-Brackmann and Sunnybrook grading system. Characteristics of the palsy and systemic comorbidities (diabetes, hypertension, herpetic infections, autoimmunity disorders, audio-vestibular symptoms) were analysed in BP and RBP patients applying Fisher exact and the Mann-Whitney U tests, while time to recovery was explored with univariate and multivariate analysis. Twenty-four patients presented two or more episodes of facial palsy, representing a recurrence rate of 7%. Associated symptoms (e.g. retroauricular pain, taste disorder, dry eye etc.) were similar between BP and RBP patients. RBP occurred at older age than primary episode (p = 0.03). Recurrence was a risk factor for delayed recovery (p = 0.02), although final facial function was similar between the two groups. In conclusion, no significant differences were found between primary BP patients and RBP patients in terms of symptoms, palsy severity and presence of comorbidities. Delayed facial nerve function recovery in RBP did not affect the final outcome. Treatment of facial nerve recurrences must be the same of the primary episode, although the presence of prodromal symptoms may alert the patient and early corticosteroid treatment may be commenced even before the onset of paresis.